Final answer:
The logical expression that represents the statement is ¬p ∧ (f ∨ h). It is equivalent to (p → ¬h) ∨ (p → f).
Step-by-step explanation:
The logical expression that represents the statement: 'The student is not on academic probation and the student got an A on the final or turned in all the homework' is:
¬p ∧ (f ∨ h)
To demonstrate that this logical expression is equivalent to (p → ¬h) ∨ (p → f), we can break it down into two parts:
Part 1: ¬p ∧ (f ∨ h) → (p → ¬h) ∨ (p → f)
We can assume the left side of the implication is true and show that the right side must also be true: If the student is not on academic probation and they got an A or turned in all the homework, then either if the student is on academic probation, they did not turn in all the homework (¬h), or if the student is on academic probation, they got an A (f).
Part 2: (p → ¬h) ∨ (p → f) → ¬p ∧ (f ∨ h)
We can assume the right side of the implication is true and show that the left side must also be true: If either if the student is on academic probation, they did not turn in all the homework (¬h), or if the student is on academic probation, they got an A (f), then the student is not on academic probation and they got an A or turned in all the homework.